Peningkatan Hasil Belajar dan Bernalar Kritis Kelas X SMAN 1 Pagak Materi Bersikap Kritis dan Bertanggung Jawab terhadap Media Massa melalui Problem Based Learning - Yoanna Francisca Dwi Purnastiti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The teaching methods applied in grade X at SMAN 1 Pagak are still lacking in variety, leading to students' low critical reasoning skills and the failure to achieve the target in the proficient and skilled categories. This research aims to improve students' learning outcomes and target achievement through the implementation of Problem Based Learning (PBL). The Classroom Action Research (CAR) was conducted in two cycles with the material "Being Critical and Responsible towards Mass Media", each consisting of four stages: planning, action, observation, and reflection. The research subjects were nine students from grade X Phase E at SMAN 1 Pagak. The research indicators included idea and information clarification, idea and information analysis, use of sources, and prioritization of relevant ideas. The results of the study showed that the Problem Based Learning (PBL) method was able to improve learning achievements: from 0% proficient, 44% skilled, 56% adequate, and 0% developing, to 56% proficient, 44% skilled, 0% adequate, and 0% developing. The results also demonstrated that the Problem Based Learning (PBL) method was able to enhance the Pancasila Student Profile (P3) character, specifically in the critical reasoning dimension. The average critical reasoning dimension increased from 60% to 80%. The recommendation is to focus on one dimension by choosing a teaching method that is both engaging and activating.